Multi-Hazard Susceptibility Analysis of Bantul Regency - Renny Laksmita Ningsih; Putri Yuko Nawang Wulan; Ahmad Harisul Haq; Fajar Nur Ihsan; Regita Wulan Kusuma; Renjis Farhan; Fashabilla Alfi; Siti Nurjanah; Eko Haryono (Universitas Pendidikan Indonesia, 2023)
The Bantul Regency area has varied landform characteristics so it is susceptible to several disasters such as landslides, earthquakes, and tsunamis. The purpose of this study was to analyze the level of susceptibility to landslides, earthquakes, and tsunamis in Bantul Regency. The method used to determine the level of susceptibility of the Bantul Regency is tiered weighting. The data used are the National Digital Elevation Model (DEM), geological and geomorphological maps of Yogyakarta, Indonesian earth map, Yogyakarta soil type map, and rainfall data. The results of this study indicate that the susceptibility of landslides in Bantul Regency tends to be high in areas with hilly reliefs, while flat areas tend to be safe. Earthquake disasters tend to be susceptible to areas that are close to faults and have high slopes. The Bantul Regency area which is close to the coastline and has a high elevation tends to be susceptible to tsunami disasters. These results can be used as planning material to increase the capacity of Bantul Regency to deal with those three disasters.